REPRESENTATION OF RACIAL DISCRIMINATION IN KASI LEMMONS’S HARRIET - ANGGI VERONIKA SIMANJORANG; SYAMSUL BAHRI (LINGUISTICA, 2022)
In this social conditions, it is undeniable that cases of discrimination still dominate actions that are still widely felt by individuals, or groups of people.  This discriminatory attitude is still often found in social, cultural, school and work life. This study aimed at identifying the kinds of racial discrimination in Illustration and dialog of script and movie biographies about Harriet Tubman and what are Nigger's resistance toward those discriminations in the movie.  This study was conducted by applying descriptive qualitative method. The sources of data were taken from the script. The research instrument was the researcher herself by using a tool including laptop and books. The results of this research showed that in Harriet movie, there were five types of discrimination with the total of verbal antagonist (37,037%), avocation (18,518%), segregation (37,037%), physical attack (7,4071%). Racial discrimination is a belief or doctrine that inherent differences among the various human races determine cultural or individual achievement, and finally discrimination found as the most dominant thing that the depict racism in the movie.